Setting the group agenda: negotiating deontic rights through directives in a task-based, oral, L2, group assessment. Issue 4 (1st October 2020) - Stephenson, Michael
ABSTRACT: The use of group-based, task-oriented, peer interaction formats in classroom and public L2 speaking tests has grown in recent years. However, these assessments have received comparatively little attention when compared to other formats such as the oral proficiency interview (OPI). In order to better understand the local exigencies of this group-based, peer interaction format, the current paper, using a Conversation Analytic (CA) methodology, explores the mechanisms through which consequences are brought about in such highly task-oriented, collaborative discourse. In doing so, I report on examinees' use of directives to shape the emerging interactional agenda and so negotiate deontic rights relative to their co-participants. There is a focus, in particular, on the turn design and sequential placement of these directives and, from this, it is shown how different linguistic formats correlate to a propensity for recipients to either endorse (that is, enact) or circumvent (ignore, challenge) the interactional agenda imposed by said directive. Finally, this paper discusses some of the implications these findings have in terms of learner and assessor training.